Clinical and genetic studies of CLCN5 mutations in Japanese families with Dent's disease. - Igarashi, T; Inatomi, J; Ohara, T; Kuwahara, T; Shimadzu, M; Thakker, R (2000)
BACKGROUND: Dent's disease is an X-linked renal tubular disorder that is characterized by low molecular weight proteinuria, hypercalciuria, nephrolithiasis, and renal failure. The disease is caused by inactivation of a renal chloride channel gene, CLCN5, that encodes a 746-amino acid protein with 12 to 13 transmembrane domains. The Japanese variant of Dent's disease has been observed to be less severe, and we have investigated two unrelated Japanese families for CLCN5 mutations. METHODS: Six patients from two unrelated families were studied. Leukocyte DNA from probands was used with CLCN5-specific primers for polymerase chain reaction (PCR) amplification of the coding region and exon-intron boundaries, and the DNA sequences of the products were determined to identify abnormalities in the gene. RNA extracted from the kidney, leukocytes, or urine sediments was used to characterize further the effects of the identified mutations. RESULTS: beta2-microglobulinuria was detected in five patients, hypercalciuria in two patients, nephrolithiasis in three patients (2 of whom were females), and one 51-year-old man had renal failure. Two novel CLCN5 mutations consisting of an a to g transition at the invariant ag acceptor splice site of intron 5 and an intragenic deletion that encompassed the region between intron 3 and intron 6 were identified. The acceptor splice site mutation led to the utilization of two alternative cryptic splice sites in exon 6 that resulted in a frameshift or skipping of the exon 6. The deletional mutation, which resulted in a loss of exons 4, 5, and 6, is predicted to lead to a loss of domains 1 through 4. Both mutations predict truncated chloride channels that are likely to result in a functional loss. CONCLUSIONS: The observations of renal failure in one male and nephrolithiasis in two females represent important new findings in this Japanese variant of Dent's disease that is associated with CLCN5 mutations. In addition, our study is the first to demonstrate the use of urinary sediment cells and renal tissue for the detection of CLCN5 transcript abnormalities. These results help to expand the spectrum of CLCN5 mutations associated with Dent's disease.